Rupture process of the 2024 Noto Peninsula earthquake inferred from strong motion, teleseismic, and geodetic data - Hiroaki Kobayashi; Tetsushi Watanabe; Kazuki Koketsu (Earth, Planets and Space)
Abstract We performed joint source inversions of strong motion, teleseismic, and geodetic data to investigate the rupture process of the 2024 Noto Peninsula earthquake. A multi-segment fault model was constructed based on the distribution of relocated aftershocks and survey results of submarine active faults. The hypocenter was located on a secondary fault subparallel to the main fault system, where preceding swarm activity had occurred. According to the inversion results, the rupture initially propagated northwestward up-dip along the secondary fault and, after approximately 6 s, migrated onto the main fault system. Moderate slips then started around the migration point on the main fault system at approximately 10 s, followed by large slips. Subsequently, the rupture propagated bilaterally, with large slips occurring simultaneously at 25–35 s in the northwestern part of the Noto Peninsula and the northeastern offshore region. In the latter region, both southeast- and northwest-dipping faults ruptured. Large slips were primarily obtained at depths shallower than approximately 8.5 km, where relatively few aftershocks occurred. Our results suggested that rupture termination at both the northeastern and southwestern ends of the fault was possibly controlled by fault geometry. The initial rupture propagation on the secondary fault and moderate-to-large slips on the main fault system appear to avoid areas where the swarm activity had occurred. The rupture primarily occurred in segments along known submarine active faults with large slips, highlighting the importance of submarine fault information for assessing future coastal earthquakes. Graphical Abstract